Theological Basis of the Hadith Teaching on the Manners of Seeking Knowledge - Elvi Khairani; Sarwadi Sulisno (Quality : Journal Of Education, Arabic And Islamic Studies, 2026)
This study examines the theological basis of the teachings of the hadith on the etiquette of seeking knowledge from an Islamic perspective. Seeking knowledge is not only considered an obligation commanded by the Prophet Muhammad (peace be upon him), but must also be carried out with good manners according to the Sunnah. The hadiths emphasize the importance of sincere intentions, sincerity, respect for teachers, and politeness during the learning process. By emulating these etiquette, students not only receive blessings and rewards but also improve their spiritual and social standing in the eyes of Allah and society. This journal uses a study approach of hadith texts and Islamic literature to emphasize that the etiquette of seeking knowledge is the main foundation in carrying out the obligation to acquire knowledge in an Islamic manner, which needs to be integrated into the Islamic religious education system. This journal aims to examine in depth the theological basis of the teachings of the hadith on the etiquette of seeking knowledge by referring to the Qur'an, the Hadith of the Prophet Muhammad (peace be upon him), and the views of authoritative Salaf scholars. This study uses a qualitative method with a library research approach. The results of this journal demonstrate that the etiquette of seeking knowledge has a strong theological basis, rooted in the concepts of monotheism, worship, and morals in Islam. Therefore, the teaching of hadith on the etiquette of seeking knowledge needs to be systematically internalized in contemporary Islamic education as a foundation for developing students' character.